How to become a better negotiator - Luecke, Richard (AMACOM/American Management Association, 2008)
A fast, powerful guide to getting what you want every time.
Revised edition of: How to become a better negotiator / James G. Patterson. 1996.
Keywords: Negotiation in business.; elektronické knihy; electronic books